RESPON ISLAM TERHADAP ISU GENDER - Helva Zuraya; Ana Rosilawati (Khatulistiwa, 2011)
Gender issues have so far dominated the topics of discussion as well as seminars. The Koran has abolishes discrimination between men and women. The Koran regards men and women as equal. Men and women are different only when it comes to playing their roles, but this does not mean one is superior to the other. Rather, men and women should respect each other.